The Innovative Thinking of Junior High School English Teaching Methods - Sun, Yue (Journal of Theory and Practice of Contemporary Education, 2024)
With the continuous promotion of the new curriculum reform process in China, English teaching in junior high schools has become the key content of the curriculum reform. In view of the current situation, relevant junior high school English teachers should carefully analyze the current English teaching methods and continue to reform and innovate. Therefore, this paper will focus on the analysis and summary of the current situation of English teaching environment in junior high schools in China, and further elaborate innovative measures to deal with the reform of English teaching in junior high schools, providing some reference significance.